2008
DOI: 10.1111/j.1479-828x.2007.00809.x
|View full text |Cite
|
Sign up to set email alerts
|

A randomised comparison between sublingual, oral and vaginal route of misoprostol for pre‐abortion cervical ripening in first‐trimester pregnancy termination under local anaesthesia

Abstract: Objective:  To compare efficacy of sublingual (S/L), oral and vaginal routes of misoprostol administration for cervical priming before suction evacuation (SE) under local anaesthesia. Methods:  In a prospective randomised clinical trial, 200 women in the first trimester of pregnancy were randomised into four groups of 50 each. Patients in control group did not receive any medication before SE while other treatment groups received 400 µg of misoprostol three hours prior to SE either by sublingual/oral or by vag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 19 publications
2
18
4
Order By: Relevance
“…The results were comparable with the study by Saxena et al and Tang et al 10,11 Tang et al, as compared the absorbtion kinetics and systemic bioavailability of misoprostol by oral, sublingual and vaginal route and vaginal route with addition of water. 12 They found that sublingual misoprostol achieved significantly higher peak serum concentrations (574.8±250.7pg/ml) than oral (287.7±144.3 pg/ml; p <0.001) or vaginal (125.2±53.8pg/ml) routes.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The results were comparable with the study by Saxena et al and Tang et al 10,11 Tang et al, as compared the absorbtion kinetics and systemic bioavailability of misoprostol by oral, sublingual and vaginal route and vaginal route with addition of water. 12 They found that sublingual misoprostol achieved significantly higher peak serum concentrations (574.8±250.7pg/ml) than oral (287.7±144.3 pg/ml; p <0.001) or vaginal (125.2±53.8pg/ml) routes.…”
Section: Discussionsupporting
confidence: 80%
“…These results were however different from those obtained by Saxena et al 10,13 The observed side effects like abdominal pain, loose motions, vaginal bleeding, nausea and vomiting were quite different from the earlier studies by Tang et al where the incidence was high which may be because of the higher and the frequent dosing used in the first study. 9,14 Vaginal bleeding in our study was less in the vaginal group than the other two groups, which could be attributed to the sustained peak plasma concentration in this route.…”
Section: Discussioncontrasting
confidence: 57%
“…Cervical preparation may decrease pain during abortion procedures as it decreases the force needed to dilate the cervix. 10 Preparation with misoprostol reduced pain from aspiration abortion compared with placebo in one study, 11 but not in another. 5 One study which found sublingual misoprostol to be more effective at causing cervical dilation than the vaginal or oral route also noted less abortion pain with this route.…”
Section: Misoprostol and Cervical Ripening And Abortion Painmentioning
confidence: 98%
“…5 One study which found sublingual misoprostol to be more effective at causing cervical dilation than the vaginal or oral route also noted less abortion pain with this route. 11 Misoprostol, however, causes more pain during the preparation period than placebo. Ibuprofen can be used during this preparation time to reduce preprocedure cramping caused by misoprostol, but this has only been found to have a benefit in multiparous women.…”
Section: Misoprostol and Cervical Ripening And Abortion Painmentioning
confidence: 98%
“…However, the data are scanty in Indian patients. [8] Hence, the present study was carried out to compare the effectiveness of 400 μ g of misoprostol through three different routes (vaginal, S/L, oral) for cervical ripening in first trimester abortion prior to VA. This study also evaluates other parameters like side effects, operative ease, and patient acceptability of various routes of administration.…”
Section: Introductionmentioning
confidence: 99%